Search found 1 match

Return to advanced search

k! * (k + 1) == (k + 1)!; How?  TOPIC_SOLVED

k!(k + 1) = (k + 1)!

How does the left simplify to the expression on the right?

(I understand what factorial is, and I can find rules for multiplying two factorials, but I don't have any rules for multiplying a sum by a factorial.)
by syntaxerror
on Wed Jul 24, 2013 6:03 pm
 
Forum: Advanced Algebra ("pre-calculus")
Topic: k! * (k + 1) == (k + 1)!; How?
Replies: 1
Views: 1170

Return to advanced search